Risk management practices in internationalization process in Malaysian research public universities / Omar Abdul Rahim - Abdul Rahim, Omar (2021)
The internationalization agenda is one of the main targets set by the government through the Ministry of Higher Education (MOHE), which is translated into the MOHE strategic plan starting with the National Strategic Plan for Higher Education (PSPTN) in 2007 until the latest Malaysia Education Development Plan (Higher Education Plan) or MEB (PT) 2015-2025. With a target of enrolling 250,000 international students by 2025, institutions of higher learning (IPT) in Malaysia have to face various challenges such as visa problems, quality of students, discipline issues, infectious diseases, and many more that may affect not only the image of HEIs and the country, but also to the local community. As HEIs deal with thousands of students from hundreds of countries, HEIs must ensure that they are prepared for any possible risks that may arise during the process of handling these international students. Therefore, it is crucial that these internationalization processes are implemented with risk management so that it can be administered systematically as the government has invested a lot of capital for international students in public HEIs through education subsidies. Risk management, according to ISO 31000: 2018, is the process of identifying, evaluating, and managing the importance of risk. It aims to monitor and control risk from occurring and ensure minimal impact in the event of a risk. All Public Universities (UA) generally need to implement risk management in University governance as it is part of the conditions of granting Autonomous status as contained in the Best University Governance Index (UGGI) Code of Best Governance Practices (CUGG). In addition, UA, which has been awarded ISO 9001: 2015 certification, has no exception to implementing risk, as the new standard has adopted the concept of risk-based thinking as a condition of re-certification. However, a study by Md. Ariff et al. (2014) against five Research Universities (RUs) that gained autonomous status in 2012 showed that none of the universities had implemented risk management. Therefore, this study set out to determine the status of risk management implementation in internationalization processes, the key success factors that led to the implementation, internationalization's risky area, and identify the suitable risk management framework in RU’s internationalization work process. For those objectives to be achieved, qualitative semi-structured interviews method targeting respondents who are directly involved in managing the international student’s processes, risk officer, staff, and also students are conducted. This method had been chosen because of the data that researcher needs are more on their experience while implementing the risk management processes. Based on the result, all RUs had risk management in place in their internationalization processes. However, there are few issues also emerged and will be discussed further in this research. The most critical success factors affecting the implementation of risk management are the risk manager/risk officer, top management, risk policy, and framework. However, there are many more factors that appear during the study. One of the most interesting findings was ISO 9001: 2015 is the most important factor driving risk management implementation in RU. While operational risk, compliance, strategy, reputation, and finance are among the high-risk categories involving the three most risky processes, namely visa process, strategic goals, and accommodation as well as the facilities provided. Finally, a new framework for managing the internationalization risk at the university is also proposed. Perhaps the finding gives a conclusion on the risk management implementation status in Malaysia Public HEIs using internationalization as the sample. Most importantly, it answered all the research objectives stated earlier.